Advancing abolitionism: why the immigration detention industry must end - Canning, Victoria (Immigration detention and social harm, 2025)
The global proliferation of the use of immigration detention poses a conundrum for those working towards the abolition of such sites. Whilst racist processes of bordering are inextricably built into immigration detention and, indeed, migration controls more broadly, harms cannot be witnessed, addressed or challenged without taking reformative steps in the shorter term. This chapter therefore unpacks these complex discrepancies. Recognising the extent to which racism and neo-colonial supremacy are embedded in detention, the chapter considers whether activists, academics and abolitionists can ever legitimately engage in reform with the structures on which such sites are built. To address this question, I highlight four harms that cannot be separated from immigration detention specifically and asylum processes more generally: autonomy harms, temporal harms, relational harms and gendered harms. From here, I describe a “trinity of tropes” that are regularly posited in relation to immigration detention and harm, before moving on to outline five points that can be employed in the wider struggle towards immigration detention abolition.